Tensile Behavior of Zeolite-filled High Density Polyethylene Annealed Composite - Purnomo Purnomo; M. Subri (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
This work is focused on an investigation of tensile behavior of natural zeolite-high density polyethylene (HDPE) annealed composites. Annealing process of injection molded  composite was performed at 90oC for 12 h. Uniaxial tensile test was conducted at constant cross head speed of 4 mm/minat room temperature (25oC). Results showed that elongation at break, ductility ratioandyield stressdecreasedwith increasingconcentration of zeolite in host matrix. While, tensile strength and Young'smodulusincreasedwith the increasing zeolite content up to 5 wt.%, and they decreased in further additions. This is due to the mechanism of stress transfer from the matrix to the particles occurs efficiently in zeolite content of 5 wt.%. Keywords:tensile strength, zeolite, HDPE, mechanical properties